2009
DOI: 10.1002/ajh.21549
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular targets associated with transformed diffuse large B cell lymphoma using highly purified tumor cells

Abstract: Follicular lymphoma (FL) frequently transforms into the more aggressive diffuse large B cell lymphoma (DLBCL‐tr), but no protein biomarkers have been identified for predictive or early diagnosis. Gene expression analyses have identified genes changing on transformation but have failed to be reproducible in different studies, reflecting the heterogeneity within the tumor tissue and between tumor samples. Gene expression analyses on Affymetrix Human Genome U133 Plus 2.0 arrays were performed, using flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…NEK2 overexpression has been recognized in various cancers, including breast cancer, lymphoma, testicular seminomas, lung cancer, and colorectal cancer, and it has been shown to correlate with an aggressive phenotype and poor prognoses for these cancers (11,(31)(32)(33)(34). A recent study reported that NEK2 silencing by shRNAs reduces tumor cell progression by interference with chromosomal segregation in human breast cancer cell lines in vitro and in fat pad xenograft mouse models, leading to aneuploidy and subsequent cell death (35).…”
Section: Methodsmentioning
confidence: 99%
“…NEK2 overexpression has been recognized in various cancers, including breast cancer, lymphoma, testicular seminomas, lung cancer, and colorectal cancer, and it has been shown to correlate with an aggressive phenotype and poor prognoses for these cancers (11,(31)(32)(33)(34). A recent study reported that NEK2 silencing by shRNAs reduces tumor cell progression by interference with chromosomal segregation in human breast cancer cell lines in vitro and in fat pad xenograft mouse models, leading to aneuploidy and subsequent cell death (35).…”
Section: Methodsmentioning
confidence: 99%
“…Gal-3 has been reported to have antiapoptotic activity in several types of tumor cells, including DLBCL cells [6][7][8] ; however, removal of cell-surface gal-3 alone with 75 g/mL GCS-100 did not decrease cell viability (Figure 2A). Thus, we asked whether removal of cell-surface gal-3 would sensitize DLBCL cells to apoptosis induced by other agents.…”
Section: Removal Of Cell-surface Gal-3 Sensitizes Dlbcl Cells To Apopmentioning
confidence: 97%
“…All specimens in this study were diagnosed according to the World Health Organization (WHO) criteria [16] including; FL, n 5 12; DLBCL-tr, n 5 6; DLBCL-GC, n 5 7; DLBCL-nonGC, n 5 10; MCL, n 5 12; CLL, n 5 15; L-MCL, n 5 6 and HCL, n 5 10. Of note, some samples (FL, n 5 12; DLBCL-tr, n 5 6) have been analyzed previously in a study where the transformation from FL to DLBCL-tr was examined [17]. Freshly frozen tumor cell suspensions were collected from the biobank at the Department of Pathology, Uppsala University Hospital (Uppsala, Sweden) (FL, DLBCL, MCL, CLL, HCL), and from the biobank at Rigshospitalet (Copenhagen, Denmark) (L-MCL).…”
Section: Collection and Isolation Of Tumor Cellsmentioning
confidence: 99%
“…The labeled cRNA was hybridized to the Human Genome U133 Plus 2.0 arrays containing 50,000 transcripts (Affymetrix). This complete procedure is described in detail previously [17,20]. All arrays included in the study passed the initial quality control, including comparison of scaling factors, background, noise, and GAPDH expression with threshold values defined by Affymetrix.…”
Section: Collection and Isolation Of Nonmalignant Tonsil B-cellsmentioning
confidence: 99%